2021
DOI: 10.1093/ajhp/zxab214
|View full text |Cite
|
Sign up to set email alerts
|

Methods used to attribute costs avoided from pharmacist interventions in acute care: A scoping review

Abstract: Purpose Cost-avoidance studies are common in pharmacy practice literature. This scoping review summarizes, critiques, and identifies current limitations of the methods that have been used to determine cost avoidance associated with pharmacists’ interventions in acute care settings. Methods An Embase and MEDLINE search was conducted to identify studies that estimated cost avoidance from pharmacist interventions in acute care s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 62 publications
0
9
0
Order By: Relevance
“…100% probability of harm), which we recognize may not always be a valid assumption and risk overinflating CA estimates given that an adverse event would not have occurred or the intervention may have ultimately been detected by another member of the healthcare team. A recent scoping review of CA from pharmacist interventions demonstrated high risk of inflation and limited assessment of probability of harm ( 38 ). We attempted to mitigate this risk with the incorporation of a sensitivity analysis using only the CA categories with the highest levels of evidence, although only five intervention categories have CA values that come from controlled studies.…”
Section: Discussionmentioning
confidence: 99%
“…100% probability of harm), which we recognize may not always be a valid assumption and risk overinflating CA estimates given that an adverse event would not have occurred or the intervention may have ultimately been detected by another member of the healthcare team. A recent scoping review of CA from pharmacist interventions demonstrated high risk of inflation and limited assessment of probability of harm ( 38 ). We attempted to mitigate this risk with the incorporation of a sensitivity analysis using only the CA categories with the highest levels of evidence, although only five intervention categories have CA values that come from controlled studies.…”
Section: Discussionmentioning
confidence: 99%
“…When incorporating financial measures, investigators are encouraged to consider defined pharmacoeconomic methods such as cost‐effectiveness, cost‐utility, cost‐benefit, or cost‐minimization studies 15 . Cost avoidance studies have been commonly reported in attempts to quantify the value of pharmacist activities, however, a recent scoping review has demonstrated that the methods are frequently flawed and report cost avoidance values that are inflated 16 . There is no consensus definition of a cost‐avoidance study, and they are generally considered to be low‐level evidence of value.…”
Section: Perspective Value Sample Measures Study Designsmentioning
confidence: 99%
“…Survey instruments can be used to characterize the quality of life, patient satisfaction, and provider satisfaction 19,20 . When attempting to demonstrate value from the healthcare or payer perspectives cost‐effectiveness and cost avoidance designs may be preferred although a quality improvement, such as improvement in clinical outcomes and improvement in vaccination rates are desirable components of value 16,17 . The provider perspective of value can be demonstrated through survey instruments and collaborative/interprofessional practice scales, such as the Assessment of Interprofessional Team Collaboration Scale (AITCS) or Team Decision Making Questionnaire (TDMQ).…”
Section: Perspective Value Sample Measures Study Designsmentioning
confidence: 99%
See 2 more Smart Citations